Analisis Logo Hari Jadi Kota Bandung ke-212: Representasi “Bangkit Bersama Untuk Bandung Juara” pada Logo Ulang Tahun Kota Bandung Ke 212 - Faisal Miftah Fadhillah; Ferry Darmawan (UNISBA Press, 2024)
Abstract. In celebration of the 212th Anniversary of the City of Bandung in 2022, the Bandung City Culture and Tourism Office is holding a logo competition to celebrate the 212th Anniversary of the City of Bandung. In the design itself, the logo must have a background regarding the process of creating the logo. This use of the logo for the 212th Anniversary of the City of Bandung provides a representation of the theme raised, namely Rising Together for Bandung to be Champion. The research objectives of this study are as follows: To find out the meaning of